Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes de primer ciclo de la carrera de Ingeniería Ambiental, de la Facultad Agropecuaria y de los Recursos Naturales Renovables de la Universidad Nacional de Loja, 2024. - Vélez Jiménez, Zulay Geraldine (2024)
The present curricular integration work aimed to analyze the relationship between the levels of the basic cognitive processes of attention and memory and reading comprehension in students of the first cycle of the Environmental Engineering degree, Faculty of Agriculture and Renewable Natural Resources, of the National University of Loja, 2024. A quantitative, descriptive, correlational and cross-sectional study was applied, with a non-experimental design, it had a sample of 27 students. The assessment instruments used were the d2 attention test, the RIAS subscale for memory, and the ICLAU instrument to measure reading comprehension. The SPSS program was applied to process data. Kendall's Tau-b was used for the correlation between variables and Pearson's linear correlation coefficient was devoted for analysis and interpretation. The results displayed that 62.96% of students have a low level of attention, which pageants difficulties in maintaining attentional focus and inhibiting distracting stimuli. In relation to memory, 55.58% had a high level, showing optimal levels for encoding, storing and retrieving information. Regarding to the reading comprehension, 77.78% got average levels, which appearance that students have moderate levels to interpret the overall information of the text, except for the appreciation level. Therefore, it is concluded that the basic cognitive processes of attention and memory are significantly related to reading comprehension, and the alternative hypothesis (H1) of the research is accepted.